Optimisation of the daily operation of a hydrokinetic-diesel generator power plant - Kusakana, K. (Proceedings of the ... Conference on the Industrial and Commercial Use of Energy (Print), 2015)
The present paper develops an optimization model for the operation of a hybrid energy system consisting of a hydrokinetic system, a battery bank and diesel generator. The optimization approach is aimed at minimizing the cost function subject to the availability of water resource, total load energy requirements as well as the diesel generator and the battery operational constraints. The main purpose of the control algorithm proposed here is to minimize the use of the diesel generator in the electricity generation process while maximizing the use of the hydrokinetic system. For simulation purpose, hourly water velocity, and load demand data for a selected rural area in South Africa have been collected and used as an input to the developed model. The economic analysis has resulted in the calculation of optimized daily operation cost of the proposed hybrid system in summer and winter conditions. The obtained results demonstrate that a substantial reduction up to 71% in the daily operation cost can be achieved using the hybrid system compared to the case where the diesel generator is used alone.